Viability of 7F2 pre-osteoblast after Sulawesi stingless bee (Tetragonula biroi) 1% propolis nanoemulsion extraction - Sitalaksmi, Ratri Maya; Amalia, Nadya Rafika; Nugraha, Alexander Patera; Budhy, Theresia Indah; Ramadhani, Nastiti Faradilla; Situmorang, Putri Cahaya; Noor, Tengku Natasha Eleena binti Tengku Ahmad; Shariff, Khairul Anuar (Majalah Kedokteran Gigi Indonesia, 2024)
Produced by a stingless bee (Tetragonula biroi) from Sulawesi Island, propolis is an active compound that requires further studies to determine its herbal-based medicinal applications. In addition, propolis is well known as a potential natural ingredient for herbal medicine with minimal side effects. The stingless honeybee, native to Sulawesi, produces propolis, a resin. Propolis from Trigona stingless bees in Sulawesi has the highest flavonoid content compared to Apis mellifera bees. Flavonoids are the most common compounds contained in propolis. Propolis from stingless bees may have the potential to stimulate osteoblast cell proliferation and be responsible for bone regeneration. The objective of this study is to investigate the viability of the 7F2 pre-osteoblast cell line after administration of the stingless bee’s 1% propolis nanoemulsion extract (PNE). A 1% PNE was formulated by maceration methods and diluted into several concentrations of 100%, 50%, 25%, 12.5%, 6.25%, 3.125%, 1.56%, and 0.78%. A particle size analysis was done to examine the particle size and zeta potential of the 1% PNE. A Tetrazolium Technique assay was carried out to examine 1% PNE application on a 7F2 pre-osteoblast cell line on days 1, 3, and 7. The highest viability of 7F2 pre-osteoblast cells was at 0.78% concentration on day 7, and the lowest viability was observed at 100% concentration on day 1, with significant differences among groups (p < 0.05). A 1% PNE with a particle size of 151.28 to 182.2 nm and a zeta potential of −32.76 mV was successfully formulated. The 1% PNE was non-toxic to 7F2 pre-osteoblast cells, with a cell toxicity limit at a concentration of 1.56%.